THE EFFECT OF COMMUNICATION SKILLS, JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT TO EMPLOYEE PERFORMANCE - Syardiansah Syardiansah; Dyah Ayu Ardianti; Rudi Septian (Universitas Islam Bandung, 2023)
This study aims to determine the effect of communication skills, job satisfaction and organizational commitment to employee performance at PT. Mopoli Raya Unit I of Langkat Regency. The sample in this study amounted to 78 respondents. Data analysis method used is multiple linear regression analysis, hypothesis testing using t test, F test, and Determination Test (R2). The results obtained by Y = 1,212 - 0,002X1 + 0,230X2 + 0,516X3, Partially, Communication Capability does not significantly influence employee performance. Job Satisfaction has a significant effect on employee performance. Organizational commitment has a significant effect on employee performance. Communication skills, job satisfaction and organizational commitment simultaneously have a significant effect on employee performance. The results of the coefficient of determination (R2) obtained by 0.348 or 34.8% communication skills, job satisfaction and organizational commitment affect the performance of employees of PT. Mopoli Raya Unit I and the remaining 65.6% is influenced by other variables.